Roads to change: The Karnali highway and occupational shift among Dalits in Nepal - Shrestha, Rama (Nepal Sociological Journal, 2025)
This study investigates occupational transformations among Dalit households in Dahikhola- Chhati, a remote village in Nepal’s Karnali Province, following the construction of the Karnali Highway. Employing qualitative methodologies and grounded in classical sociological theories: Functionalism, Marxism, and Symbolic Interactionism, the research explores how improved infrastructure strengthens economic diversification and social mobility in historically marginalized communities. The data for the study were collected through in-depth interviews, case studies, and field observations with 51 Dalit households. The findings reveal a significant shift away from hereditary, caste-based occupations such as blacksmithing and tailoring toward wage labor, small-scale entrepreneurship, and professional careers. This transition is accompanied by increased income diversity, expanded market access, gender empowerment, and greater participation in education and migration. The Karnali Highway has not only physically connected geographically isolated communities but also has symbolically disrupted entrenched caste hierarchies. By analyzing these lived experiences, the study illustrates how infrastructure can act as a catalyst for both economic empowerment and identity reconstruction. It depicts the role of mobility, not only physical but also social and symbolic, in reshaping the aspirations and trajectories of Dalit communities. This research, hopefully, contributes to development and sociological discourse by demonstrating that inclusive infrastructure projects can serve as transformative forces for social justice and caste equity in post-caste rural societies.